Sistem Informasi Pendataan Karyawan pada PT. Waskita Karya Banda Aceh (Journal Innovations Computer Science, 2023)
Employee Information System is an essential data processing activity at PT. Waskita Karya, aims to increase the directness and accessibility of information about employees. This research focuses on analyzing problems related to employees and data management mechanisms at PT. Waskita Karya, by designing an Employee Data Collection Information System using the PHP and MySQL programming languages. The research objective involves an in-depth understanding of employee problems and data management at PT. Waskita Karya, with results in the form of developing applications supporting the Employee Information System using PHP and MySQL. Data collection methods were carried out through library studies involving literature from library books and other scientific works, and field studies using interviews and direct observation of research objects. The employee data collection process is carried out by an administrative staff member who is assisted by two administrative staff in the employee sector to record and input employee data. The research results show that the Employee Information System at PT. Waskita Karya has been implemented according to procedures using PHP and MySQL-based computer technology as a database. The research results show that the Employee Information System at PT. Waskita Karya Banda Aceh has succeeded in integrating appropriate operational procedures and utilizing computer-based technology with PHP and MySQL programming languages as the database backend.